Orientasi Penegakan Hukum terhadap Perlindungan dan Keadilan Korban Kekerasan dalam Rumah Tangga - Dwi Putri Melati (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Domestic Violence (DV) is a criminal act that not only causes physical and psychological suffering to victims, but also reflects the weak orientation of victim protection within the criminal justice system. This study focuses on examining the orientation of law enforcement toward the protection and justice of domestic violence victims in Decision Number 149/Pid.Sus/2023/PN Tjg, as well as analyzing the extent to which the retributive justice approach is capable of fulfilling victims’ substantive rights. The study aims to analyze the position of victims within the criminal justice process, assess the effectiveness of the retributive approach in realizing justice for victims, and examine the urgency of implementing restorative justice as a reform of law enforcement orientation. This research employs a normative juridical method using statutory, case, and conceptual approaches. Data were collected through library research involving legislation, court decisions, books, and relevant scientific journals. The findings reveal that victims in the case were still positioned merely as instruments of proof in the evidentiary process, while psychological recovery, restitution, and sustainable protection were not considered primary concerns in the judicial decision. The relatively lenient sentence imposed on the perpetrator also indicates that substantive justice for victims has not yet been fully achieved. This study concludes that reforming the orientation of law enforcement through a restorative justice approach is necessary in order to establish a criminal justice system that is more victim-oriented and substantively just.